Stigma and Associated Correlates of Elderly Patients With Parkinson's Disease - Hou, Miaomiao; Mao, Xiaowei; Hou, Xiaojun; Li, Kunpeng (Frontiers in Psychiatry, 2021)
Background: Stigmatizing experiences are common in Parkinson’s Disease (PD), and appear to provide a negative contribution to the quality of life. Our aim of this study was to investigate the extent of stigma and its predictive factors in patients with PD from our hospital in Shanghai, China. Methods: In 276 individuals with PD (135 women, 141 men), stigma was measured by the 24-item Stigma Scale for Chronic Illness (SSCI). Multivariate linear regression model was used to assess predictors of stigma including demographics (age, gender), disease duration, stage (Hoehn & Yahr Scale), motor function (Unified Parkinson’s Disease Rating Scale Part 3, UPDRS-III), non-motor symptoms (Non-Motor Symptoms Scale, NMSS), cognitive level (Mini-mental State Examination, MMSE), as well as anxiety (Hamilton Anxiety Scale, HAMA) and depressive disorders (Hamilton Depression Scale, HAMD-24). Results: The total score of SSCI was (49.9 ± 14.3). 48.5% of the patients checked Rarely to Sometimes. For the total sample, the full model accounted for 47.8% of the variance in stigma (p < 0.05). Higher UPDRS-III scores, longer course of disease, younger age, tremor dominant subtype, and higher depression scores were significantly associated with stigma among individuals with PD. Conclusion: Our finding suggested a mild to moderate level of stigma in patients with PD. Tremor dominant subtype, longer course of disease, younger age, severe motor symptoms and depression are the predictors of stigma in PD.